2019
DOI: 10.5578/turkjsurg.4162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local hemostatic effect of microporous polysaccharide hemospheres products in thyroid surgery: a prospective randomized controlled study

Abstract: Objective: Bleeding is a rare and dangerous complication of thyroid surgery. One of the hemostatic agents used during surgery are microporous polysaccharide hemospheres (MPH) which are local hemostatic agents acquired from purified potato starch. The aim of this study was to evaluate the efficiency of two MPH, produced with different biotechniques, in decreasing hemorrhages and drainage following thyroidectomy. Material and Methods: A statistical power analysis predicted that totally 20 patients per each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Despite promising animal studies 14,15 and a recent retrospective study of MPH use in ALT donor sites where the use of MPH was associated with lower rates of seroma formation and were associated with earlier drain removal, 19 we did not detect a significant difference in postoperative drain output, seroma development, or hematoma development with the use of MPH. This is consistent with other randomized controlled trials that found no significant improvement in postoperative surgical site drainage with MPH after mastectomy or total thyroidectomy 23,24 . On the other hand, in an unpublished retrospective cohort of more than 100 patients performed at our institution prior to initiating this trial, we found that MPH use was associated with decreased rates of ALT donor site seroma formation and earlier surgical drain removal.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite promising animal studies 14,15 and a recent retrospective study of MPH use in ALT donor sites where the use of MPH was associated with lower rates of seroma formation and were associated with earlier drain removal, 19 we did not detect a significant difference in postoperative drain output, seroma development, or hematoma development with the use of MPH. This is consistent with other randomized controlled trials that found no significant improvement in postoperative surgical site drainage with MPH after mastectomy or total thyroidectomy 23,24 . On the other hand, in an unpublished retrospective cohort of more than 100 patients performed at our institution prior to initiating this trial, we found that MPH use was associated with decreased rates of ALT donor site seroma formation and earlier surgical drain removal.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other randomized controlled trials that found no significant improvement in postoperative surgical site drainage with MPH after mastectomy or total thyroidectomy. 23,24 On the other hand, in an unpublished retrospective cohort of more than 100 patients performed at our institution prior to initiating this trial, we found that MPH use was associated with decreased rates of ALT donor site seroma formation and earlier surgical drain removal. MPH has shown some benefit in certain surgical procedures such as improved hemostasis following brain tumor resection in a case series of 33 patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…There are a limited number of studies investigating the effectiveness of polysaccharide-based HAs 5–7 . Therewithal, HAs can lead to some clinical complications such as inflammatory reactions or tumor-like mass lesions that have also been reported 8–10 .…”
mentioning
confidence: 99%